Post-traumatic knee osteoarthritis; the role of inflammation and hemarthrosis on disease progression - Evers, Bob J.; Van Den Bosch, Martijn H. J.; Blom, Arjen B.; van der Kraan, Peter M.; Koëter, Sander; Thurlings, Rogier M. (Frontiers in Medicine, 2022)
Knee injuries such as anterior cruciate liamgent ruptures and meniscal injury are common and are most frequently sustained by young and active individuals. Knee injuries will lead to post-traumatic osteoarthritis (PTOA) in 25-50% of patients. Mechanical processes where historically believed to cause cartilage breakdown in PTOA patients. But there is increasing evidence suggesting a key role for inflammation in PTOA development. Inflammation in PTOA might be aggravated by hemarthrosis which frequently occurs in injured knees. Whereas mechenical symptoms (joint instability and locking of the knee) can be successfully treated by surgery, there still is an unmet need for anti-inflammatory therapies that prevent PTOA progression. In order to develop anti-inflammatory therapies for PTOA, more knowledge about the exact pathophysiological mechanisms and exact course of post-traumatic inflammation is needed to determine possible targets and timing of future therapies.